A new species of the cardinalfish genus Siphamia (Perciformes, Apogonidae) from West Papua, Indonesia - Gon, Ofer; Allen, Gerald R.; Erdmann, Mark V.; Gouws, Gavin (Zootaxa, 2014)
A new species of the cardinalfish genus Siphamia is described from specimens collected in the Province of West Papua, Indonesia, at depths of 50–72 m. Siphamia papuensis n. sp. has a striated light organ which makes it a member of the S. tubifer species group. Within this group it is closely related to S. argentea, sharing with the latter 13 pectoral-fin rays, 9 developed gill rakers and an irregular pattern of yellowish green bars on the body. It differs from S. argentea in having an incomplete lateral line and in lacking dark marks on the head, and at the origin and end of the dorsal-fin and anal-fin bases, as well as the absence of red spots along the light organ and along the back. Japanese records of S. tubulata are reidentified as S. argentea, and new locality records for S. argentea and S. stenotes are reported. Analysis of sequence data from a 16S rDNA fragment revealed the clear separation of S. papuensis n. sp., S. argentea and other included Siphamia species (S. jebbi, S. tubifer and S. stenotes).